Can One Size Fit All? Exploring the possibility of one API for XML processing. - Obasanjo, Dare (XML journal :the ultimate enterprise resource.)
Traditionally, APIs for processing XML have been categorized according to whether they're designed for processing entire XML documents loaded in memory, such as the W3C DOM, or for processing XML in a streaming, forward-only fashion, such as SAX. However, these divisions do not fully represent the various classes of APIs for processing XML.